THE FUTURE OF THE AGE-FRIENDLY HEALTH SYSTEM AT UCSF - Walter, L. (Innov Aging, 2017)
San Francisco is the 17th most rapidly aging city in the U.S. and 19% of our seniors live alone. Many seniors become homebound in San Francisco due to the many hills and stairs. To address these challenges the UCSF Division of Geriatrics has developed innovative, multidisciplinary clinical programs to provide high quality care for frail, seriously ill older adults in our community. Results of our clinical programs (e.g., decreased ED visits, decreased hospitalizations, improved patient satisfaction, decreased costs) will be discussed as we shift from costly hospital-centric care to value-based population health with a focus on improving geriatric care for our rapidly expanding older population.